Analyzing Speech Act on Public Sentiment in Responses to President Prabowo’s New Policies Post on Instagram - Selly Sitompul; Octavia Amelia; Albert Zebua; Elyana Manurung; Meisuri Meisuri (STIKes Ibnu Sina Ajibarang, 2025)
In the digital era, social media platforms like Instagram have become critical arenas for public discourse, especially in political communication. This study investigates public sentiment and expressive speech acts in Instagram comments responding to two of President Prabowo’s key policy announcements: the Free Nutritious Meal Program and the policy of direct bank transfers for regional ASN teacher allowances. Guided by Searle’s theory of speech acts, particularly expressive acts such as thanking, complementing, congratulating, deploring, condoling, apologizing, and welcoming, the study analyzes 60 purposively selected comments, 30 for each policy. The findings show that deploring dominates the discourse, with 67% in the meal program post and 73% in the ASN allowance post, indicating prevailing negative sentiment marked by criticism, disappointment, and frustration. Positive speech acts such as complimenting and thanking were present but marginal. These results highlight the importance of transparent policy implementation and the need for improved public communication strategies to address citizen concerns more effectively on digital platforms.